Perkembangan Reduksi Asap Rokok dalam Rumah Menuju Kabupaten/Kota Layak Anak: Fakta dari Survei Demografi dan Kesehatan Indonesia 2012 dan 2017 - Puspitasari, Mardiana Dwi; Arifa, Riza Fatma (Research and Development Agency Ministry of Home Affairs, 2023)
In 2017, only about 26.68 percent of Indonesian households were tobacco-free. Acute respiratory infections (ARIs) in children under the age of 5 have been linked to indoor tobacco smoke pollution. According to the Presidential Regulation number 25 of 2021, some indicators that should be met for the establishment of a child-friendly city/municipal (KLA) are child's rights to health and family environment. Data from the 2012 and 2017 Indonesia Demographic and Health Surveys (IDHS) was used to examine progress made in achieving tobacco-free households by estimating indoor tobacco smoking at the urban-rural area and regional levels. T-test analysis was used to determine the statistical significance. Findings revealed a higher prevalence of indoor tobacco smoking in rural areas. Over time, the prevalence of indoor tobacco smoking in Indonesian rural areas decreased by 0.84 percent. Between 2012 and 2017, there was no significant reduction in Kalimantan, Nusa Tenggara, or Maluku-Papua. Furthermore, Sulawesi experienced a significant increase of approximately 4.54 percent. From 2012 to 2017, the prevalence of indoor tobacco smoking was higher in households with children under the age of five, home crowding, poor households, and households with a low education household head. Therefore, interventions should focus on rural areas. Municipal governments in Sulawesi, Kalimantan, Nusa Tenggara, and Maluku-Papua should be more concerned about indoor tobacco smoke pollution. Raising family awareness about the dangers of indoor tobacco smoke pollution could be targeted at households with children under the age of 5, overcrowded households, low-income households, and households with a low-education household head.